2011
DOI: 10.1002/app.35537
|View full text |Cite
|
Sign up to set email alerts
|

Ion imprinted beads embedded cryogels for in vitro removal of iron from β‐thalassemic human plasma

Abstract: Molecular recognition based Fe3+ imprinted poly(GMA‐MAC) (MIP) beads embedded PHEMA composite cryogel was prepared for selective removal of Fe3+ ions from β‐thalassemia patient plasma. The precomplexation was achieved by the coordination of Fe3+ ions with N‐methacryloyl‐(L)‐cysteine methyl ester (MAC‐Fe3+). MIP beads were prepared by dispersion polymerization in the presence of MAC‐Fe3+ complex and glycidyl methacrylate (GMA) monomer. Then the MIP beads were embedded into poly(hydroxyethyl methacrylate) (PHEMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…They measured the surface area, swelling degree and maximum adsorption capacity of composite cryogel as 76.8 m 2 /g, 7.7 g H 2 O/g cryogel and 2.23 mg/g. They also calculated the relative selectivity of composite cryogel towards Fe 3+ ions and found that it was 135.0, 61.4, and 57.0 times greater than Ni 2+ , Zn 2+ , and Fe 2+ ions, respectively [86].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…They measured the surface area, swelling degree and maximum adsorption capacity of composite cryogel as 76.8 m 2 /g, 7.7 g H 2 O/g cryogel and 2.23 mg/g. They also calculated the relative selectivity of composite cryogel towards Fe 3+ ions and found that it was 135.0, 61.4, and 57.0 times greater than Ni 2+ , Zn 2+ , and Fe 2+ ions, respectively [86].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…All biomaterials have to meet the certain criteria before use for living systems. Depending on desired end use the blood compatibility, tissue compatibility, carcinogenicity, toxicity and mechanical stability tests must be performed using developed bioma-terials (Denizli and Piskin 1995, Denizli 1999, Ergün et al 2012). If a material contact with blood, firstly the small molecules are floated on surface (i.e.…”
Section: Hp Removal Studies From Human Plasmamentioning
confidence: 99%
“…As a whole, this is useless presentation of the textural characteristics of the cryogels. Cryogels with molecular-imprinted polymers have attracted increased attention because of significant enhancement of the selectivity of the materials used as adsorbents [234,243]. Additionally, functionalisation of cryogels can be used for the same purposes.…”
Section: Diffusion Of Small Molecules Polymers Proteins and Cells Wmentioning
confidence: 99%